Young and Novice Donors Are More Susceptible To Hemodynamic Adverse Effects during Blood Donation - Mrigendra Amatya, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Young and Novice Donors Are More Susceptible To Hemodynamic Adverse Effects during Blood Donation